Le Corbusier : an atlas of modern landscapes - Cohen, Jean-Louis (Thames & Hudson, 2013)
This volume examines Le Corbusier's relationship with the topographies of five continents, in essays by thirty of the formeost scholars of his work and with contemporary photographs by Richard Pare.